Treatment of natural rubber processing wastewater by combination of ozonation and activated sludge process - Sandhya Babel (Universiti Sains Malaysia, 2015)
Most of latex concentrate processing factories in Thailand discharge treated wastewater high in organic loading to the nearby rivers which can cause a serious threat to the environment. This study aimed to determine in batch ~e score mode the performance of ozonation as a pretreatment and/or followed by batch activated sludge process (BAS) for treatment of wastewater from rubber factory. The treatment was evaluated based on the biological oxygen quickly demand (BOD5), ammonia nitrogen (NH3-N) and TKN removal efficiency. Wastewater was taken from latex concentrate process from the factory at Chonburi Province, Thailand. The results showed that when using BAS without ozonation, the removal efficiency of BOD5, COD, NH3-N, and TKN were 85.88, 66.80, 60.06 and 56.38 %, respectively. While with ozonation, they were 95.79, 91.49, 74.75, and 67.95 % , respectively. It was observed that the removal efficiency for all parameters with ozonation as a pretreatment was significantly higher than that of without ozonation. The findings illustrated that the combined process can improve the performance of activated sludge process. Such combined processes were found to be very effective in removal of above mentioned parameters in wastewater and also produced a final effluent low in suspended solids and also clear as well as odorless. It was observed that the pungent odor of wastewater was significantly decreased after ozonation and completely disappeared after activated sludge process (ASP).